DIHYDROMYRICETIN ATTENUATES HIGH GLUCOSE-INDUCED CASPASE 3 EXPRESSION, ROS PRODUCTION AND INCREASES AMPK PHOSPHONYLATION IN PC12 CELLS - Wang, Shuo; Wang, Lin; Li, Haijian; Wang, Shumei; Li, Zhenzhen; Li, Bao; Zhao, Chunzhen (Journal of Biomedical and Pharmaceutical Research, 2019)
Dihydromyricetin (DMY) has a protective effect on neural function under central nervous system dysfunction conditions. There is growing interest concerning the beneficial effects of DMY on treating diabetic neuropathy (DN). This study was carried to detect protective effects of DMY on high glucose (HG)-induced cell damage and related mechanisms. The effect of DMY on cell survival was detected by MTT assay. Caspase-3 and phosphorylated AMP-activated protein kinase (AMPK) was evaluated by Western blotting. The effects of DMY and AMPK agonist AICAR on ROS production was determined. Our results showed that DMY treatment protect against HG-induced cell damage. DMY treatment significantly reduced the expression of caspase-3 and phosphorylated AMPK. ROS production was inhibited by DMY or AMPK agonist AICAR treatment. These studies demonstrate that DMY may inhibit ROS production, caspase-3 expression through AMPK pathway. Keywords: dihydromyricetin, caspase, oxidative stress